Hyperspectral Imaging for Clinical Applications - Yoon, Jonghee (Biochip Journal, 2022)
Measuring morphological and biochemical features of tissue is crucial for disease diagnosis and surgical guidance, providing clinically significant information related to pathophysiology. Hyperspectral imaging (HSI) techniques obtain both spatial and spectral features of tissue without labeling molecules such as fluorescent dyes, which provides rich information for improved disease diagnosis and treatment. Recent advances in HSI systems have demonstrated its potential for clinical applications, especially in disease diagnosis and image-guided surgery. This review summarizes the basic principle of HSI and optical systems, deep-learning-based image analysis, and clinical applications of HSI to provide insight into this rapidly growing field of research. In addition, the challenges facing the clinical implementation of HSI techniques are discussed.
Keywords: Clinical application; Disease diagnosis; HyperSpectral; Hyperspectral imaging techniques; Image guided surgery; Image-analysis; Pathophysiology; Spatial features; Surgical guidance; Tissues optics; Clinical application; Disease diagnosis; Hyperspectral imaging; Image analysis; Image-guided surgery; Tissue optics